What are we learning from business training and entrepreneurship evaluations around the developing world? - David J. McKenzie; Christopher Woodruff (Institute for the Study of Labor (IZA), 2012)
Business training programs are a popular policy option to try to improve the performance of enterprises around the world. The last few years have seen rapid growth in the number of evaluations of these programs in developing countries. We undertake a critical review of these studies with the goal of synthesizing the emerging lessons and understanding the limitations of the existing research and the areas in which more work is needed. We find that there is substantial heterogeneity in the length, content, and types of firms participating in the training programs evaluated. Many evaluations suffer from low statistical power, measure impacts only within a year of training, and experience problems with survey attrition and measurement of firm profits and revenues. Over these short time horizons, there are relatively modest impacts of training on survivorship of existing firms, but stronger evidence that training programs help prospective owners launch new businesses more quickly. Most studies find that existing firm owners implement some of the practices taught in training, but the magnitudes of these improvements in practices are often relatively modest. Few studies find significant impacts on profits or sales, although a couple of the studies with more statistical power have done so. Some studies have also found benefits to microfinance organizations of offering training. To date there is little evidence to help guide policymakers as to whether any impacts found come from trained firms competing away sales from other businesses versus through productivity improvements, and little evidence to guide the development of the provision of training at market prices. We conclude by summarizing some directions and key questions for future studies.
Keywords: O12; J16; L26; M53; 330; business training; consulting; randomized experiments; firm productivity; Führungskräfteentwicklung; Unternehmensberatung; Wirkungsanalyse; Unternehmenserfolg; Produktivität; Entwicklungsländer